SEDIMENTOLOGY AND GEOCHEMISTRY OF TRIASSIC TURBIDITIES OF SEMANGGOL AND SEMANTAN FORMATIONS, PENINSULAR MALAYSIA - SAJID, ZULQARNAIN (2021)
An integrated study comprising the sedimentological and geochemical analysis was conducted on two deep marine depositional systems in Peninsular Malaysia, namely the Semanggol Formation, which is located in the NW part of Western Belt and the Semantan Formation which is extensively located throughout the Central Belt. A total of 9 lithofacies (Fsg1-Fsg9) from Semanggol Formation and 14 lithofacies (F1-F14) from Semantan Formation were identified which constitute four facies groups: I) Conglomerate dominate facies (Fsg1-Fsg2 and F1-F4) comprising of debris flow/concentrated high-density turbidites, II) Sand dominated facies (Fsg3-Fsg6 and F5-F10 ) consisting of high-low density turbidites, III) Chaotic unit of mudstone/siltstone to fine sandstone dominated facies (Fsg7 and F11-F12) comprises mass transport deposit (MTD) and IV) Mud dominant facies (Fsg8-Fsg9 and F-13-14) which include thin-medium to thick-bedded mudstone generated by hemipelagic suspension fallout process.